Sectional Fixed Orthodontic Appliance for Management of a Pseudo Class III Malocclusion. Case Report (Bangladesh Journal of Medical Science, 2024)
Background: Proper diagnosis and treatment planning are the first steps in the management of pseudo-Class III malocclusion.Case Presentation: An 11 years old male patient with pseudo- class III malocclusion.Conclusion: A class I molar with average overjet and overbite was achieved with a sectional fixed orthodontic appliance.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 262-265